The next leadership team : how to select, build, and optimize your top team - Keil, Thomas, 1970 February 6-; Zangrillo, Marianna (Routledge, 2023)
"CEOs and organizational leaders are only as strong as the teams they build. And yet it is surprising how little practical advice there is for senior leaders on how to create, build and optimize their teams. Step up The Next Leadership Team. Illustrated with real-life examples from interviews with CEOs, C-Suite members, and headhunters throughout, The Next Leadership Team explains how senior leaders can improve the performance of their leadership teams by identifying clear team approaches, associated team member profiles, and by leading that team. These ideas are brought to life with case studies and interviews with well-known corporations such as ABB, Allianz, Amazon, AXA, Best Buy, Capita, Danone, Deutsche Telekom, Ferrari, Freudenberg, Haier, Hilti, HSBC, Holcim, Huawei, Logitech, Microsoft, Nestlé, Netflix, Nokia, Nordea, Schneider Electric, Tata, Wipro, and Zurich Insurance. The book is an invaluable resource for CEOs and senior executives who need to build and develop leadership teams to drive success in the organizations they lead. It is also relevant to headhunters who are involved in the appointments of members of senior leadership teams"--